Towards Successful Learning Within North-South Joint Ventures Operating in Sub-Saharan Africa:: An Exploratory Study - Chrysostome, Elie; Su, Zhan (Journal of Comparative International Management, 2002)
North-South joint ventures are initiated more and more nowadays. One justification for their creation is the acquisition of new know-how, with the aim of developing new competencies that favour a better competitiveness. Nevertheless, strategic learning in a North-South joint venture context still remains a poorly known area. The present research proposes examining the learning practices used by these joint ventures to see if they develop strategic competencies. The results of the research show that these practices are characteristic of vicarious learning and that new developed competencies are not profoundly strategic. The research therefore proposes a much more profound learning model that ultimately leads to the development of strategic competencies.